Analysis and comparison of performance characteristics of catalytic converters - Mohiuddin, A. K. M.; Nurhafez, Muhammad (2005)
Experiment is carried out to analyze the performance characteristics and behavior of the three-way ceramic monolith catalytic converters (TWCC) especially its efficiency in reducing the amount of pollutants. Experiment is also conducted to compare the performance of two ceramic converters of different hydraulic diameter, channel length and cell density on conversion efficiencies and pressure drop. By observing the results, suggestions on the considerable design geometries for catalytic converter properties are made. Emission test on engine test bed with converter installed and how engine-operating conditions would influence the performance of catalytic converter is investigated. The test is done at various engine speeds and at different air-to-fuel ratio. After completing the test, the converters were cut to extract the substrate or ‘honeycomb’ inside the housing and being analyzed for microstructure and materials composition using Scanning Electron Microscopy (SEM) and Energy Dispersive Analysis(EDX).